A Review on Public Rental Housing Under Neoliberal Urbanism: From Welfare to Precarity - Santi Vidyandani; Joko Adianto (Jurnal Permukiman, 2026)
This paper investigates the transformative role of Public Rental Housing (PRH) in addressing housing precarity, drawing on a systematic review of scholarly literature. It critically analyzes how neoliberal governance and housing commodification have eroded the foundational promise of PRH to deliver secure, affordable, and socially inclusive homes. The study delineates the multidimensional nature of housing precarity encompassing tenure insecurity, economic vulnerability, and social exclusion while simultaneously underscoring the emancipatory potential of PRH when structured through equitable and participatory frameworks. Comparative insights from Europe, Asia, and the Global South reveal the pitfalls of residualized housing regimes and the enduring promise of rights-based, de-commodified alternatives. These findings carry significant implications for emerging contexts such as Indonesia, where state-led housing provision must grapple with market logics and democratic deficits. The paper calls for a reconfiguration of PRH as a universal, tenure-secure institution anchored in long-term leases, democratic governance, and robust legal protections. Ultimately, the study contends that reimagining PRH not as a residual safety net but as a fundamental pillar of social citizenship is imperative to resist deepening precarity in contemporary urban housing landscapes.